WNK3 maintains the GABAergic inhibitory tone, synaptic excitation and neuronal excitability via regulation of KCC2 cotransporter in mature neurons - Lim, Wee Meng (2022)
The activation of chloride (Cl-)permeable gamma (γ)-aminobutyric acid type A(GABAA) receptors induces synaptic inhibition in mature and excitation in immature neurons. This developmental "switch" in GABA function controlled by its polarity depends on the postnatal decrease in intraneuronal Cl- concentration mediated by KCC2, a member of cation-chloride cotransporters (CCCs). The serine-threonine kinase WNK3 (With No Lysine [K]), is a potent regulator of all CCCs and is expressed in neurons. Here, we characterized the functions of WNK3 and its role in GABAergic signaling in cultured embryonic day 18 (E18) hippocampal neurons. We observed a decrease in WNK3 expression as neurons mature. Knocking down of WNK3 significantly hyperpolarized EGABA in mature neurons (DIV13-15) but had no effect on immature neurons (DIV6-8). This hyperpolarized EGABA in WNK3-deficient neurons was not due to the total expression of NKCC1 and KCC2, that remained unchanged. However, there was a reduction in phosphorylated KCC2 at the membrane, suggesting an increase in KCC2 chloride export activity. Furthermore, hyperpolarized EGABA observed in WNK3-deficient neurons can be reversed by the KCC2 inhibitor, VU024055, thus indicating that WNK3 acts through KCC2 to influence EGABA . Notably, WNK3 knockdown resulted in morphological changes in mature but not immature neurons. Electrophysiological characterization of WNK3-deficient mature neurons revealed reduced capacitances but increased intrinsic excitability and synaptic excitation. Hence, our study demonstrates that WNK3 maintains the "adult" GABAergic inhibitory tone in neurons and plays a role in the morphological development of neurons and excitability.